New results on harmonies trees - Lu, Hui-Chuan; Fu, Hung-Lin (Utilitas Mathematica, 2007)
In this paper, we mainly obtain a couple of new constructions for constructing harmonious trees from smaller sequential trees. Subsequently, we obtain two new classes of harmonious trees called palm tree and firework. As a consequence of adjoining an even number of paths, we disprove an earlier claim by Cahit [1] in investigating harmonious p-stars.